ANALISIS BEBAN KERJA KARYAWAN DIVISI ADMINISTRASI KJPP EDI RIANTO DAN REKAN CABANG GERSIK - Afifuddin Zhuhri; Nina Aini Mahbubah (Universitas Riau Kepulauan, 2021)
Kjpp Edi Rianto and Partners is a service enterprise engaged in appraisal business services as well as consultants in property appraisal. There was problem identified in term of workers’ excess workload which causes performance to be felt to be less than optimal. Along with the development of the company and requests for appraisal from the assignor, this results in the occurrence of Overtime in the ongoing work process. Workload Analysis is a method that is often used by companies or institutions in measuring and determining the optimal amount of workforce, after observing and determining the level of productivity with the Work Sampling calculation method, from the observations, the workload data received by Surveyor 1 is obtained. (132%), Surveyor 2 (141%), and Surveyor 3 (135%), the suggestion given is to add 3 workforces of surveyors, this can reduce the workload of workers, originally Surveyor 1, whose workload was originally 132%. to 66%, Surveyor 2 whose workload was originally 141% to 70.5%, and Surveyor 3 whose workload was originally 135% to 67.5%.